PENGARUH JUMLAH PENGHASILAN MARGIN PEMBIAYAAN MURABAHAH DAN ISTISHNA TERHADAP LABA PERUSAHAAN PERBANKAN DI INDONESIA - Nurba Ash Khairunnisa (Khazanah Multidisiplin, 2020)
The purpose of this studdy wasto deetermine theeffect off murabahah dan istisna financing margin income simultaneously on the profits of Islamic bank companies in Indonesia. The miethod useed iis descriiptive methiod. The typ of researc date uses quantitative data types. Sources of research data used in this study are secondary data sources obtained from the financial statements of PT. Bank Muamalat Indonesia originating from www.bi.go.id. Analysiis ofi the date used is descriptive analysis, simple regression analysis and multiple linear regression using the te teist dan fi est wiiith ia quantitative approach that uses secondary data types in the form of quarterly financial statements published by PT.Bank Muamalat Indonesia for the 2014-2016 period. The analysis techniqueused is descriptive analysis, multipli linearegression analyisis, multiplie regresion analysiys, simple correlation analysis, multiple correlation analysis, determination analysis, t test analysis and F tes for data proocessing used SPSS Windows 16.00 and MiccrosoftExcel 2010 as a tool. . The results of the three variables research are:(1) murabahah margin income is obtained ttable> tcount (1,158> -0,331) meaning thiat theire iis a negative and insignificant influience beitween murrabahah margiin iincome oon company profits. (2) Istishna MarginRevenues 'obtained by the value ttable> tcount (1.158> 0.315) means thait theire iis no siignificant positive efect betwieen istisna margin earnings' ons company profits. (3) Murabahah and istishna margin income 'obtained byÂ the value of Ftable> Fcalculation (0,2,228> 0,91) means that there is an insignificant positive effect between murabahah and istishna margin income' on company profits.